Kroatisches Schweign
This program focuses on Croatia as a new state, examining its direction under Franjo Tudjman two years after gaining international recognition. At the time of this broadcast Croatia has begun to lose sympathy as a victim of Serbian aggression and is increasingly seen as an aggressor, reluctant to come to terms with its own fascist past. Tudjman's policy in Bosnia, the historical revisionism of his HDZ party, and the reintroduction of the fascist monetary unit of the Ustasa state all contribute to the scrutiny of the new Croatia. The silence of prominent Croatian politicians is criticized and contrasted by dissidents interviewed such as Slavko Goldstein, publisher, Ivan-Zvonimir Cicak, and Mira Ljubic-Lorger, Dalmatian Action.